Biophotonics in veterinary medicine: the first steps toward clinical translation - Cugmas, Blaž; Spīgulis, Jānis (SPIE, 2019)
In this paper, we analyzed the current situation and the potential of biophotonics and biomedical optics in veterinary medicine. Promising optical techniques such as optical coherence tomography, pulse oximeter, and hyperspectral imaging have been clinically translated into human medicine. But even though human and small animal medicine share personalized and state-of-the-art approach, biophotonics remains rarely exploited in the canine and feline medicine. However, there are some biophotonics studies in veterinary oncology which addressed tumor diagnosis (skin and subcutaneous tumors), prognosis (lymphoma), and therapy (clear surgical margins). Visible and near-infrared spectroscopy served for measuring various physiological parameters related to circulation, and photobiomodulation therapy was often used for the management of wounds, skin conditions, and orthopedic problems. In the research, the most popular clinically translated technique is thermography which was applied for the diagnosis of orthopedic problems and diseases as infections and hyperthyroidism. The future optical devices for small animals such as dogs and cats should be robust and resilient to damage (e.g., due to biting, chewing), offering user-friendly and short measurements. In veterinary oncology, biophotonics could replace invasive fine-needle aspiration procedure. The potential of a pulse oximeter for pet monitoring has yet to be explored. What is more, photobiomodulation efficiency should be tested in an extensive clinical (in vivo) study. The technique would be very beneficial in dentistry which currently requires expensive and risky anesthesia.
Keywords: biophotonics; biomedical optics; veterinary medicine; clinical translational; small animals; pulse oximeter; optical coherence tomography; dogs; Research Subject Categories::NATURAL SCIENCES::Physics::Atomic and molecular physics